Students' Science Process Skills in using Worksheets Integrated with Entrepreneurship - Muhammad Nizaar (STAI Hubbulwathan Duri, 2022)
The waste processes skill is an essential skill to overcome environmental pollution problems. Unfortunately, teachers cannot yet train student skills due to the lack of a specific worksheet for specific activities. Waste processing activity would be more meaningful if it were integrated with entrepreneurship. This research aims to develop a natural science worksheet integrated to entrepreneurship that can train students' science processes skills through waste management activity. This research uses the developmental research method of ADDIE type. This research sample was junior high school students in Mataram. The data analysis of validity results uses the Aiken V index. The result of the Aiken V index from the material experts was V =0.84, categorized as very good, and the result from the worksheet design experts was V=0.83, categorized as very good. The observation reliability of science processes skills was analyzed using a Percentage of Agreement (PA). It was derived with a PA = 0.85, meaning that it meets the standard result of good observation. Students' science processes skill was observed in three activities, they are: making compost fertilizer, making handicraft products, and SWOT identification activity. Natural science worksheet integrated to entrepreneurship can train students to be skillful in making compost fertilizer and handicraft products. Meanwhile, the students consider that SWOT identification activity is still strange for them. Hence, as much as 10% of students have not been skilled yet in performing SWOT identification. The teachers need to be more active in arranging waste management, be it in school or assigning tasks to manage waste at home.